2022
DOI: 10.1186/s12916-022-02266-8
|View full text |Cite
|
Sign up to set email alerts
|

Promoting deceased organ and tissue donation registration in family physician waiting rooms (RegisterNow-1): a pragmatic stepped-wedge, cluster randomized controlled registry trial

Abstract: Background The shortage of available organs for life-saving transplants persists worldwide. While a majority support donating their organs or tissue when they die, many have not registered their wish to do so. When registered, next of kin are much more likely to follow-through with the decision to donate. In many countries, most people visit their family physician office each year and this setting is a promising, yet underused, site where more people could register for deceased organ donation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…4 Prior literature has suggested that the need for culturally competent interventions associated with opportunities for registration immediately after intervention could help improve the overall organ donation registration rates, but this remains a poorly understood area with few appropriate educational materials and interventions available. [4][5][6] This study attempts to bridge the gap by assessing the knowledge, attitudes, and beliefs toward organ donation as well as other factors affecting organ donation registration among Asian Americans in a large and diverse city and developing culturally competent educational material. We conducted surveys to identify factors associated with low organ donation registration among Asian Americans, developed an educational video informed by our findings, and then assessed the efficacy of this educational video to increase knowledge of organ donation to ultimately increase donor registrations among Asian Americans.…”
Section: Introductionmentioning
confidence: 99%
“…4 Prior literature has suggested that the need for culturally competent interventions associated with opportunities for registration immediately after intervention could help improve the overall organ donation registration rates, but this remains a poorly understood area with few appropriate educational materials and interventions available. [4][5][6] This study attempts to bridge the gap by assessing the knowledge, attitudes, and beliefs toward organ donation as well as other factors affecting organ donation registration among Asian Americans in a large and diverse city and developing culturally competent educational material. We conducted surveys to identify factors associated with low organ donation registration among Asian Americans, developed an educational video informed by our findings, and then assessed the efficacy of this educational video to increase knowledge of organ donation to ultimately increase donor registrations among Asian Americans.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies showed that healthcare professionals with positive attitudes towards organ donation are more likely to begin the organ donation process by seeking and obtaining consent from potential donor families 8. Recently, some reviews demonstrated that primary care interventions, for example, delivering organ donation information during practices and annual health check by trained general practitioners and staff, can significantly improve the organ donation registration rates,9 with more similar models were under trial 10 11. These indicated that doctors would play a more active role in organ donation promotion in the future, and they should be more prepared for it.…”
Section: Introductionmentioning
confidence: 99%